THE DEFINITION OF THE CONCEPT OF «NATIONAL INTERESTS» AND FACTORS OF THEIR FORMATION - Гарбар, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The author considers the aspects and structure-forming factors affecting the formation, development, variability, and determination of national interests of the states that exist in the system of international relations. The author formed a list of the most significant factors influencing the state interests. It is  proved  that the concept of «national interests» is variable and essentially anarchic, especially in the process of globalization, which interconnects all the components in the system of interstate relations even more. The new definition of the term «national interests» was proposed on the basis of its  comprehensive understanding.